JAK inhibitors differentially modulate B cell activation, maturation and function: A comparative analysis of five JAK inhibitors in an in-vitro B cell differentiation model and in patients with rheumatoid arthritis - Frede, Natalie; Lorenzetti, Raquel; Hüppe, Janika M; Janowska, Iga; Troilo, Arianna; Schleyer, Marei-Theresa; Venhoff, Ana C.; Voll, Reinhard E.; Thiel, Jens; Venhoff, Nils; Rizzi, Marta (Frontiers in Immunology, 2023)
Janus kinase (JAK) inhibitors have been approved for the treatment of several immune-mediated diseases (IMIDs) including rheumatoid arthritis (RA) and psoriatic arthritis and are in clinical trials for numerous other IMIDs. However, detailed studies investigating the effects of different JAK inhibitors on B cells are missing. Within this study, we therefore aimed to characterize the effect of JAK inhibition on the B cell compartment. To this end, we investigated the B cell compartment under JAK inhibition and compared the specific effects of the different JAK inhibitors tofacitinib (pan-JAK), baricitinib (JAK1/2), ruxolitinib (JAK1/2), upadacitinib (JAK1/2) as well as filgotinib (selective JAK1) on in-vitro B cell activation, proliferation, and class switch recombination and involved pathways. While B cell phenotyping of RA patients showed an increase in marginal zone (MZ) B cells under JAK inhibition, comparison with healthy donors revealed that the relative frequency of MZ B cells was still lower compared to healthy controls. In an in-vitro model of T-cell-independent B cell activation we observed that JAK1/2 and selective JAK1 inhibitor treatment led to a dose-dependent decrease of total B cell numbers. We detected an altered B cell differentiation with a significant increase in MZ-like B cells and an increase in plasmablast differentiation in the first days of culture, most pronounced with the pan-JAK inhibitor tofacitinib, although there was no increase in immunoglobulin secretion in-vitro. Notably, we further observed a profound reduction of switched memory B cell formation, especially with JAK1/2 inhibition. JAK inhibitor treatment led to a dose-dependent reduction of STAT3 expression and phosphorylation as well as STAT3 target gene expression and modulated the secretion of pro- and anti-inflammatory cytokines by B cells. Thus, JAK inhibition has a major effect on B cell activation and differentiation, with differential outcomes between JAK inhibitors hinting towards distinct and unique effects on B cell homeostasis.